Human security and international law : prospects and problems - Von Tigerstrom, Barbara, 1969- (Studies in international law (Oxford, England) ;, 2007)
Aims to evaluate human security as a concept that could be used in the analysis of international law, and to determine what insights about a human security approach might be gained by considering it from the perspective of international law.